Immunoglobulin Variations and Risk Factors Linked to Pregnancy Loss - Haraj, Mohammed A.Ameer; Al-Mansoori, Mohammed Obaid; Al-Obaidi, Rajwan Jawad (Indonesian Journal on Health Science and Medicine, 2025)
Objectives: To investigate the immunological changes, demographic risk factors, and potential correlations between Toxoplasma gondii infection and abortion incidence. Methods: A comprehensive cross-sectional study was conducted on 22 participants, analyzing IgG and IgM antibody levels, demographic characteristics, and histological changes across different age groups. Immunological markers, residence patterns, cat contact, and meat consumption were evaluated using statistical analyses. Results: Significant immunological variations were observed: IgG levels escalated from 51.25 IU/ML (healthy individuals) to 310.25 IU/ML (two abortion history), IgM levels demonstrated complex fluctuations across abortion categories, Undercooked meat consumption emerged as the most critical risk factor (OR: 2.5, p=0.001), Cat contact (OR: 1.6, p=0.016) and rural residence (OR: 1.1, p=0.012) were secondary risk factors, Age group 26-30 years demonstrated the highest pregnancy and abortion variability. Conclusions: Toxoplasma gondii infection demonstrates complex immunological responses correlated with abortion history, with dietary and environmental factors significantly influencing infection risk. The study underscores the need for targeted screening and preventive strategies in high-risk populations. Highlights:  IgG levels increase with abortion history; IgM shows variable patterns. Undercooked meat, cat contact, and rural living raise infection risk. Women aged 26–30 show highest variability in pregnancy outcomes. Keywords: Toxoplasma gondii, Immunoglobulins, Abortion, Risk Factors, Seroprevalence